Assessing oracy skills in online courses - Liashenko, Iryna (Berdyansk State Pedagogical University, 2023)
This academic article explores the intricacies of assessing oracy skills online within the context of online courses. While online learning has been growing in popularity, with many educational institutions transitioning to this mode of delivery, there remains a lack of empirical insight into designing online courses that account for the right assessment. The study seeks to address this gap by investigating the challenges and strategies involved in assessing oracy skills online. The article highlights the multifaceted nature of oracy assessment, which involves assessing oral language and communicative competence. Additionally, assessing oracy skills requires flexibility, as students mature and move from one age period to another. The challenges of online assessment are also discussed, including academic dishonesty, which can hinder fair assessment. Plagiarism, identity verification, and cheating are all identified as key challenges in online assessment. Moreover, students may experience a lack of motivation, insufficient and unrealistic information, and inadequate communication with their instructors as additional barriers in online learning. In response to these challenges, the article outlines various strategies and technologies that can be employed to assess oracy skills online. These include using formative online tests, which provide quick feedback and help build confidence and maintain practice, as well as summative tests that stem from taking formative tests. Additionally, the article suggests that educators should focus on positive student perceptions and outcomes in online learning to develop better practices. Overall, this article highlights the importance of understanding the intricacies of assessing oracy skills in online courses and provides insights into the challenges and strategies involved in this process. By taking into account the various factors that can impact online assessment, educators can develop more effective and engaging online courses that promote student success.
Keywords: Oracy skills; assessing oracy; assessing online; distance learning; communication